2022
DOI: 10.1111/bph.15866
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal alterations turn the gut hormone GLP‐2 into an antagonist with gradual loss of GLP‐2 receptor selectivity towards more GLP‐1 receptor interaction

Abstract: Background and Purpose To fully elucidate the regulatory role of the GLP‐2 system in the gut and the bones, potent and selective GLP‐2 receptor (GLP‐2R) antagonists are needed. Searching for antagonist activity, we performed systematic N‐terminal truncations of human GLP‐2(1‐33). Experimental Approach COS‐7 cells were transfected with the human GLP‐2R and assessed for cAMP accumulation or competition binding using 125I‐GLP‐2(1‐33)[M10Y]. To examine selectivity, COS‐7 cells expressing human GLP‐1 or GIP recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Because GLP‐2 is a low potency agonist of the GLP‐1R (Gadgaard et al, 2022), and N‐terminal truncations of GLP‐2 result in increased binding to the GLP‐1R (Gabe et al, 2022), we wanted to test how the Ala and Trp substituted GLP‐2 variants affected the selectivity of the peptides and therefore included experiments with the human GLP‐1R. Several variants did not activate the GLP‐1R, but [G4A] , [G4W] , [S5A] , [S5W] , [F6A] , [F6W] and [S7A] did, although with much lower potencies and efficacies than native GLP‐2 (EC 50 of 79 nM and efficacy of 89% relative to GLP‐1 for 1 μM) (Figure 5a‐g).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because GLP‐2 is a low potency agonist of the GLP‐1R (Gadgaard et al, 2022), and N‐terminal truncations of GLP‐2 result in increased binding to the GLP‐1R (Gabe et al, 2022), we wanted to test how the Ala and Trp substituted GLP‐2 variants affected the selectivity of the peptides and therefore included experiments with the human GLP‐1R. Several variants did not activate the GLP‐1R, but [G4A] , [G4W] , [S5A] , [S5W] , [F6A] , [F6W] and [S7A] did, although with much lower potencies and efficacies than native GLP‐2 (EC 50 of 79 nM and efficacy of 89% relative to GLP‐1 for 1 μM) (Figure 5a‐g).…”
Section: Resultsmentioning
confidence: 99%
“…A previous Ala scan of GLP‐2[A2G] showed that Ala substitutions in the N‐terminus resulted in less GLP‐2R activation (DaCambra et al, 2000). Furthermore, the truncated metabolite GLP‐2(3‐33) has been shown to be a partial agonist of the GLP‐2R (Gabe et al, 2022; Thulesen et al, 2002). These studies emphasize the importance of the N‐terminus for proper GLP‐2R activation, in line with what has previously been shown for other members of the class B1 family (Gabe et al, 2018; Hansen et al, 2016; Smit et al, 2021; Sparre‐Ulrich et al, 2016; van der Velden et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanism may be related to GLP-2-dependent activation [ 57 ], where low insulin and high glucagon formed in type 1 diabetes promote GLP-2 secretion in the intestine, increasing GLUT-2 abundance in the BBM. The GLUT-2 transporter performs various other physiological functions, such as stimulating intestinal mucosal growth and resistance to intestinal barrier damage following an inflammatory response [ [58] , [59] , [60] ]. In a type 2 diabetes model, hyperglycemia, hyperinsulinemia, and proglucagon confer an opposite effect due to decreased GLP-2 expression.…”
Section: The Links Between Glut-2 and Diabetes Pathogenesismentioning
confidence: 99%